Translation ethics wikified: How far do professional codes of ethics and practice apply to non-professionally produced translation? - Drugan, Joanna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Translation involves ethical decision-making in challenging contexts. Codes of practice help professional translators identify ethical issues and formulate appropriate, justifiable responses. However, new and growing forms of community translation operate outside the professional realm, and substantial differences exist between the two approaches. How relevant, then, are professional codes in the new contexts? What alternative ‘codes’ (stated or implicit) have been developed by the new groups? The content of professional codes is compared here to a broad range of community approaches to identify themes common across both, and areas where the new community might be making an original contribution. This reveals different priorities in the professional and non-professional codes. Community translation initiatives have found novel solutions to some ethical problems and challenges, particularly in self-regulation and community policing, improved interpretation of code content, an emphasis on shared values rather than individual rights, and strong mentoring.